Access to α‐ and β‐Hydroxyamides and Ureas Through Metal‐Catalyzed C≡N Bond Hydration and Transfer Hydration Reactions. Issue 31 (5th July 2021) - Crochet, Pascale; Cadierno, Victorio
Abstract: The hydration of nitriles is an important transformation because the resulting primary amides present a huge number of applications in synthetic organic chemistry, as well as industrial and pharmaceutical interest. Metallic compounds (complexes, oxides, and nanoparticles) are known to catalyze the hydration of nitriles by activating the nitrile substrate, the water molecule, or both partners, upon coordination. In this Minireview article, the application of metal‐based catalysts in the hydration of α ‐ and β ‐hydroxynitriles and cyanamides is comprehensively discussed. Compared to more classical organonitriles, little attention has been paid to the hydration of these particular class of substrates despite the synthetic relevance of the respective carboxamides, i. e. α ‐/ β ‐hydroxyamides and ureas. Transfer hydration strategies, in which a water surrogate is employed to convert the C≡N group into the C(=O)NH2 one, are also covered. Abstract : Catalytic approaches to synthetically useful α ‐hydroxyamides, β ‐hydroxyamides and ureas from the corresponding organonitriles, i. e. α ‐hydroxynitriles, β ‐hydroxynitriles, and cyanamides, respectively, are reviewed. Strategies in which the carboxamide C(=O)NH2 moiety of these molecules is generated by direct hydration of the C≡N unit of the nitriles, or by transfer hydration employing a water surrogate (aldoximes or amides), within both homogeneous and heterogeneous systems, are discussed.